Subsolidus behavior of niobian rutile from Vezna, Czech Republic: A model for exsolutions in phases with Fe2+ >> Fe3+ - Cerny,P.; Novak,M.; Chapman,R.; Masau,M. (Journal of the Czech Geological Society, 2000)
Niobian rutile crystallized in the Vezna I pegmatite in three generations: niobian rutile I associated with beryllian cordierite, beryl, zircon, xenotime-(Y) and monazite-(Ce), transitional into niobian rutile II in close vicinity of small pollucite-, lepidolite- and elbaite-bearing pods, and niobian rutile III in fissures with ferrocolumbite III, niobian titanite and pyrochlore-microlite. Exsolution of the niobian rutile I and II into depleted rutile and titanian ferrocolumbite is extensive. Exsolution possibly proceeded in several, presumably temperature-controlled stages. Relics of primary homogeneous niobian rutile are preserved in most crystals of generation I, but some of them and those of generation II, all perceptibly enriched in Mn, are completely exsolved. Oxide minerals of the last generation III could have been mobilized and redeposited from compositionally similar, Mn-enriched, porous aggregates of intergrowths I and II. The primary homogeneous rutile phase corresponds to rutile with 34 to 38 mol. % of ferrocolumbite component and a negligible proportion of Fe3+(Nb,Ta)O4. The depleted rutile phase shows as little as 16 mol. % ferrocolumbite, whereas the TiO2 content of the exsolved titanian ferrocolumbite may drop to values as low as 5 mol. %. Heterovalent substitutions in niobian rutile are accomplished by (Fe,Mn,Mg)2++1(Nb,Ta)5++2Ti4+-3, Fe3++1 (Nb,Ta)5++1Ti4+-2, Sc3++1 (Nb,Ta)5++1 Ti4+-2, and (Fe,Mn,Mg)+2+1 W6++1 Ti4+-2. With negligible and undecipherable additional substitutions, reverse mechanisms control ferrocolumbite: (Fe,Sc)3++3 (Nb,Ta)5++3 (Fe,Mn,Mg,Ca)2+-2 (Nb,Ta)5+-4, and (Ti,Zr,Hf)4++3 (Fe,Mn,Mg,Ca)2+-1 (Nb,Ta)5+-2. Exsolution concentrates Mg, Mn, Fe2+, Fe3+, Sc, Zr, Hf, U, Nb, Ta and W in the exsolved ferrocolumbite. In relative terms, rutile conserves Sn, Fe2+, Fe3+, Ta, and Fe3+ relative to Fe2+, whereas Mn and Nb are preferred by the columbite structure. The ZrO2 content or primary homogeneous niobian rutile is ≤0.34 wt. % but the exsolved ferrocolumbite contains as much as 2.11 wt. % along with ≤0.16 wt. % HfO2. These concentrations confirm that Zr and Hf must be considered significant minor elements in niobian rutile from granitic environments. Considerable enrichment in Mg, ≤0.34 wt. % MgO in primary homogeneous niobian rutile and ≤2.16 wt. % MgO in exsolved ferrocolumbite, can be presumed a local feature, reflecting contamination of the pegmatite by serpentinite wallrock.
Keywords: Rutile; ferrocolumbite; niobium; tantalum; zirconium; hafnium; order-disorder; exsolution; granitic pegmatite; Czech Republic